(untitled) (TAJ: Journal of Teachers Association, 2018)
With the advent of industrialization, accelerated social violence, increasing road traffic accident and increasing use of machineries trauma has become the leading cause of mortality and disability. Considering trauma abdominal trauma is one where early diagnosis and accurate assessment and timely intervention can save the life of the victim in most of the instances. This is a prospective observational study that represents the experience of 100 consecutive patients of blunt abdominal trauma with suspected intra-abdominal injuries admitted in surgical words of RMCH, Rajshahi. The most of the patients were male (87%) and in active phase of life. RTA (53%) was the most common cause of blunt abdominal trauma and majority of the patients (38%) arrived in the hospital within 7-24 hours. Major clinical signs of intra-abdominal injuries were signs of peritonitis. The main investigation done was plain X-ray abdomen (71%) in erect posture, of which 55% cases showed free gas under the done of the diaphragm. Out of 100 cases 77 patients were operated upon and 23 patients were managed conservatively. The incidence of hollow viscus injury (57%) was higher than solid organs (36%) injury but only five patients came out to be a negative laparotomy. Of all operated cases fifty one were recovered uneventfully and only twenty three patients developed various postoperative complications. The most of the patients (40%) left the hospital within 11-14 days. Seven patients died on the day of admission but total mortality was nine (9%) in number. TAJ 2015; 28(2): 7-14